A New Fast Navier-Stokes Solver and Its Parallel Implementation - Hj. Mohd. Ali, Norhashidah; Abdullah, Abdul Rahman (Malaysian Journal of Computer Science, 1997)
The Four-point Explicit Decoupled Group(EDG) iterative method was briefly introduced in solving a well known coupled system of elliptic partial differential equations in CFD (Computational Fluid Dynamics), in particular, the steady Navier-Stokes equations. This new method is compared with the Alternating Group Explicit (AGE) scheme. The numerical experiments carried out confirm the superiority of the former method over the latter in terms of execution time. The parallel implementation of the new method intended for a shared memory parallel computer is investigated and discussed.